Pelatihan Google Classroom Sebagai Media Mengajar saat Work From Office bagi Guru SDN 02 Puyung Di Masa Pandemi Covid-19 - Permana, Erwin Putera; Rosalia, Novita Dewi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
It is important that Google Classroom training activities are carried out so that they can help teachers and educators understand about Google Classroom and E-Learning-based learning media. This is supported by the fact that the training participants are teachers who need assistance because they are still laymen and do not understand E-Learning. The goal is that teachers can provide learning through flexible media, not only focused on face-to-face teaching methods. In addition, it can improve the quality of the teaching and learning process and can facilitate teachers and students in dealing with problems in the teaching and learning process in elementary schools. The method used during training is giving and explaining the material and practicing it. Based on a series of training activities on the use of Google Classroom learning media that all participants are more familiar with digital-based learning media and can use them for online learning in the form of WFH and WFO during the Covid-19 pandemic and future learning.